CURRENT THEORETICAL AND METHODOLOGICAL PROBLEMS OF ENSURING EQUAL RIGHTS AND OPPORTUNITIES IN THE FIELD OF LABOR - O. O., Kovalenko (Київський національний університет імені Тараса Шевченка, 2022)
The purpose of the article is to characterize the current theoretical and methodological problems of ensuring equal rights and opportunities in the field of labor. The author emphasizes the disregard by representatives of the Ministry of Health of the conceptual basis for the construction of labor law norms - the principle of unity and differentiation, which, precisely in order to prevent the violation of equal rights and opportunities for labor rights, provided for the existence of common starting positions for the legal regulation of relations in the field of labor and , at the same time, taking into account objective factors that do not allow equal use of rights and opportunities or that require increased protection of the employee's person due to the special danger of the influence of production factors on his health, provides, as a result, special additional guarantees for the realization of their rights .It is concluded that at the stage of denationalization of labor legislation, preparation of a new legal framework for the regulation of relations in the field of labor, methodological approaches in the construction of legal norms should be maintained. All norms of labor legislation should be based on common positions, but take into account the individual characteristics of the subjects of legal relations.

Метою статті є характеристика актуальних теоретико-методологічних проблем забезпечення рівних прав і можливостей у сфері праці. Автор наголошує на ігноруванні представниками Міністерства охорони здоров’я концептуальної засади побудови норм трудового права – принципу єдності і диференціації, який, як раз із метою недопущення порушення рівних прав і можливостей трудових прав, передбачив наявність спільних вихідних позицій для правового регулювання відносин у сфері праці і, разом з тим, із урахуванням об’єктивних факторів, що не дозволяють на рівних користуватись правами і можливостями або що вимагають підвищеного захисту особи працівника через особливу небезпеку впливу виробничих факторів на його здоров’я, передбачає, внаслідок цього, спеціальні додаткові гарантії реалізації їхніх прав. Робиться висновок, що на етапі дерадянізації трудового законодавства, підготовці нової бази правового регулювання відносин у сфері праці, мають бути витримані методологічні підходи у вибудовуванні норм права. Всі норми трудового законодавства мають виходити із спільних позицій, але брати до уваги особливості суб’єктів правовідносин.
АКТУАЛЬНІ ТЕОРЕТИКО-МЕТОДОЛОГІЧНІ ПРОБЛЕМИ ЗАБЕЗПЕЧЕННЯ РІВНИХ ПРАВ І МОЖЛИВОСТЕЙ У СФЕРІ ПРАЦІ
Keywords: unity and differentiation of labor law norms; young professionals; professional qualities; level of knowledge; educational level; gender equality in labor relations; women's rights; gender inequality.; єдність і диференціація норм трудового права; молоді фахівці; професійні якості; рівень знань; освітній рівень; гендерна рівність у трудових відносинах; права жінок; гендерна нерівність.